PENINGKATKAN PRESTASI BELAJAR AKUNTANSI DENGAN TEKNIK BIMBINGAN SELF CONTRACTING AND SELF REINFORCEMENT (Dinamika Pendidikan, 2013)
The objective of the study was to improve students’ learnig achievement to complete the Accounting cycle at service companies through the guidance techniques of self- contracting and self reinforcement on the 1st semester students of XI PE 3class in SMK Negeri 1 Pemalang in the academic year of 2011/2012. The previous assessments of students’ learning results in completing the Accounting Cycle for service companies showed low average, it was only 65.40, whereas the minimum score was 75. The low achievement could be initiated by students’ low motivation and activities. They were reluctant to study because of the domination of lecturing method. Thus, it was needed a more appropriate method to develop the exemplary, to give motivation, and also to give opportunity for students to be optimal in learning. The learning process through the guidance technique of self- contracting and self reinforcement could increase the students’ achievement with the average of daily score was 75.98, it was higher than the KKM (minimum score) and the students’ completeness was 77.50% which increased about 32.50%